1960
DOI: 10.1104/pp.35.5.645
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Synthesis in Corn Endosperm Tissue Cultures. II. Effect of Certain Inhibitory and Stimulatory Agents

Abstract: In a previous paper (7), the advantages of corn endosperm tissue cultures as an experimental tool in attacking the problem of anthocyanin synthesis were pointed out. The general culture conditions, the identity of the pigments, and the requirement for light were reported in the same paper.Thimann and Radner (11,12) have shown that anthocyanin synthesis in Spirodela is inhibited by -purine and pyrimidine antagonists, by certain sulfurcontaining compounds and certain amino acids. They also demonstrated (13) that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1964
1964
1993
1993

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…When used in combination with benzimidazole in the light, riboflavin severely inhibited all activities of the hypocotyl and was lethal to most of the lower segments. In agreement with our results, Straus (9) has shown that riboflavin inhibited anthocyanin synthesis in cultured corn endosperm tissue.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…When used in combination with benzimidazole in the light, riboflavin severely inhibited all activities of the hypocotyl and was lethal to most of the lower segments. In agreement with our results, Straus (9) has shown that riboflavin inhibited anthocyanin synthesis in cultured corn endosperm tissue.…”
Section: Discussionsupporting
confidence: 83%
“…The relationship between the level of differentiation of a tissue and the sensitivity of anthocyanin synthesis to 8-azaguanine was further supported by the observation that the anthocyanin was formed well up into the hypocotyl arch (meristematic region) when 8-azaguanine was present in the medium. Straus has reported that 8-azaguanine caused a slight enhancement of anthocyanin formation in cultured corn endosperm tissue (9). The corn endosperm seems to approximate more nearly the condition of the meristematic tissue of segment 1 than the mature Spirodela plants used by Thimann et al (10)(11)(12)(13).…”
Section: Discussionmentioning
confidence: 97%
“…Bibb and Hagen, 1972;Creasy et al , 1965;Hartmann, 1970;Hess, 1966;Longevialle, 1969;Margna etal., 1969;Mohr and Bienger, 1967;Mohrand Senf, 1966;Rossiter and Barrett, 1970;Straus, 1960). Inhibitors of protein synthesis may block the accumulation of one flavonoid, but not another, in the same tissue.…”
Section: Inhibitor Studiesmentioning
confidence: 99%
“…Glutathione also promoted anthocyanin synthesis and PAL activity in internode segments not treated with Co'* (Tab, 2), while cysteine showed no such effect (Tab, 3), Glutamic acid promotes anthocyanin synthesis in tissue cultures derived from corn endosperms (Straus 1960), Glutathione contains a glutamyl side-chain which might play a certain role during anthocyanin synthesis, NEM, a sulfhydryl reagent, bad no effect on anthocyanin synthesis and PAL activity at low concentrations but at 0,1 mM and 1 mM it inhibited both processes up to 47% and 70%, respectively (Fig, 2), Addition of 1 mM cysteine or glutathione alleviated the inhibitory effect of NEM in the internode segments (Tab, 4), These results further show involvement of sulfhydryl groups in anthocyanin synthesis.…”
Section: Resultsmentioning
confidence: 98%